2009
DOI: 10.1212/wnl.0b013e3181a55f65
|View full text |Cite
|
Sign up to set email alerts
|

Impairments in memory and hippocampal function in HIV-positive vs HIV-negative women

Abstract: Objective: Neurocognitive studies of HIV typically target executive functions dependent on frontostriatal circuitry. The integrity of medial temporal systems has received considerably less attention despite high hippocampal viral load. Studies also predominately involve HIVϩ men, though HIVϩ women may be at increased risk for cognitive dysfunction due to the high prevalence of psychosocial/mental health problems and lower educational attainment. Our aim was to conduct a preliminary investigation of episodic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
118
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(123 citation statements)
references
References 19 publications
4
118
0
1
Order By: Relevance
“…35 A previous WIHS functional MRI study suggests that the deficits in verbal learning and memory observed in this study might reflect hippocampal dysfunction. 11 Compared to HIV-uninfected controls, HIV-infected women showed hippocampal hyperactivation during verbal encoding and hippocampal hypoactivation during recall. 11 Alterations in hippocampal function during verbal encoding and recall were associated with lower HVLT performance.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…35 A previous WIHS functional MRI study suggests that the deficits in verbal learning and memory observed in this study might reflect hippocampal dysfunction. 11 Compared to HIV-uninfected controls, HIV-infected women showed hippocampal hyperactivation during verbal encoding and hippocampal hypoactivation during recall. 11 Alterations in hippocampal function during verbal encoding and recall were associated with lower HVLT performance.…”
Section: Resultsmentioning
confidence: 97%
“…11 Compared to HIV-uninfected controls, HIV-infected women showed hippocampal hyperactivation during verbal encoding and hippocampal hypoactivation during recall. 11 Alterations in hippocampal function during verbal encoding and recall were associated with lower HVLT performance. Alterations in prefrontal cortex also likely contribute to the observed deficit in delayed verbal memory, because HIV-associated deficits in verbal memory are characterized by deficits in executive control of encoding and retrieval mechanisms, 25 a pattern consistent with frontal-subcortical involvement.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Among HIVinfected individuals, problematic alcohol use is associated with worse HIV health outcomes [e.g., 2,5,7,8,[11][12][13][14][15][16][17][18][19] which ostensibly result in increased HIV symptom severity and lower overall quality of life. Adding to the clinical profile, HIV disease progression (i.e., heightened symptom burden) is commonly associated with neurocognitive impairment [24][25][26][27][28]. Given the high prevalence of alcohol problems among HIV-infected individuals coupled with its observed negative impact on memory functioning, routine screening for problematic alcohol use in HIV care settings is thus imperative [14,89].…”
Section: Discussionmentioning
confidence: 99%
“…HIV disease progression poses significant risk for compromised cognitive efficiency (e.g., executive dysfunction) and memory functioning (as indexed by neuropsychological testing) [24][25][26][27][28], and although antiretroviral therapy (ART) can reduce neurocognitive impairment [29], mild forms still persist in a large proportion of individuals with HIV [30,31]. Of note, cognitive impairment, and memory dysfunction more specifically, is associated with worse treatment outcomes among HIV-infected individuals [27,[32][33][34] and is known to reduce the effectiveness of interventions aimed at optimizing adherence and reducing risk behavior [35].…”
Section: Introductionmentioning
confidence: 99%